Femtosecond Pulse Fiber Laser at 1.91 mu m using MoSe2/PVA-based Evanescent Field Interaction - Lee, Jinho; Koo, Joonhoi; Lee, Ju Han; Jhon, Young Min; Lee, Junsu (2017 OPTO-ELECTRONICS AND COMMUNICATIONS CONFERENCE (OECC) AND PHOTONICS GLOBAL CONFERENCE (PGC), 2017)
We experimentally demonstrate a femtosecond pulse fiber laser operating at 1.91 mu m, which incorporates a Mu omicron Se-2/PVA-based saturable absorber (SA). The SA was implemented by depositing a MoSe2/PVA composite film onto a side-polished fiber platform. Using the evanescent field interaction of the oscillating beam with the MoSe2/PVA, stable femtosecond pulses could be readily obtained from a Tm-Ho-codoped fiber ring cavity.